2014
DOI: 10.1007/s00192-014-2561-0
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis comparing immediate and delayed catheter removal following uncomplicated hysterectomy

Abstract: The existing evidence from RCTs suggests that delayed catheter removal following uncomplicated hysterectomy increases the incidence of postoperative bacteriuria and symptomatic UTI but reduces the risk of recatheterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 30 publications
0
28
0
2
Order By: Relevance
“…Finally, it is relevant to assess patient's wellbeing on catheter removal. Studies have reported that patients experience more urethral or vesical pain with prolonged catheterisation . In our study, eight women (9.6%) from the DCR group requested catheter removal a few hours after surgery because of unbearable discomfort, which is from a patient's perspective an important finding against prolonged catheterisation.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Finally, it is relevant to assess patient's wellbeing on catheter removal. Studies have reported that patients experience more urethral or vesical pain with prolonged catheterisation . In our study, eight women (9.6%) from the DCR group requested catheter removal a few hours after surgery because of unbearable discomfort, which is from a patient's perspective an important finding against prolonged catheterisation.…”
Section: Discussionmentioning
confidence: 70%
“…Studies have reported that patients experience more urethral or vesical pain with prolonged catheterisation. 9 In our study, eight women (9.6%) from the DCR group requested catheter removal a few hours after surgery because of unbearable discomfort, which is from a patient's perspective an important finding against prolonged catheterisation. On the other hand, women who had a catheter in place until the next morning reported on average a low VAS specific for the catheter (2.9, SD 2.9).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Every attempt is made to remove the catheter for an early trial of void, as this is associated with better infectious outcomes and earlier patient mobilization after surgery. A systematic review and meta‐analysis of early vs delayed catheter removal after uncomplicated hysterectomy showed increased incidence of positive urine culture and symptomatic UTI, as well as a longer time to first ambulation in the delayed removal group . In addition, self‐catheterization is preferred over indwelling catheterization because of lower counts of bacterial colonization .…”
Section: Discussionmentioning
confidence: 99%
“…However, studies evaluating the association between these procedures and UTI attributed the relationship to the placement of an in-dwelling catheter during and after surgery. 19,20 The incidence of post-hysterectomy UTI is reported to be increased following delayed catheter removal (24 hours after the procedure). 19 In the present cohort, all patients had undergone catheterization.…”
Section: Discussionmentioning
confidence: 99%